2002
DOI: 10.1590/s0103-90162002000300002
|View full text |Cite
|
Sign up to set email alerts
|

Decoquinate, lasalocid and monensin for starter feeds and the performance of holstein calves to 20 weeks of age

Abstract: The large utilization of coccidiostats in dairy herds has raised the question regards the best product to use, based on better animal performance. Sixty-four Holstein calves were randomly assigned to four treatments at 10 (±4) d of age to evaluate calf performance when fed approved coccidiostats available on the market in Arizona, USA. Calves received a dry calf starter without (control) or with one of the following coccidiostats: lasalocid, 30 mg kg-1; decoquinate, 19 mg kg-1; and monensin, 30 mg kg-1. Calves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 9 publications
1
6
0
2
Order By: Relevance
“…According to Nussio et al (2002), inclusion of monensin in the starters for calves may have a negative influence on solid feed intake. These authors observed lower intakes of starter with monensin during the period after weaning, suggesting that the negative effect may occur when the animal presents the rumen partly developed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Nussio et al (2002), inclusion of monensin in the starters for calves may have a negative influence on solid feed intake. These authors observed lower intakes of starter with monensin during the period after weaning, suggesting that the negative effect may occur when the animal presents the rumen partly developed.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, positive effects are observed in animal growth in early weaning program systems with the use of ionophores (Fitzgerald and Mansfield, 1984;Watkins et al, 1987;Anderson et al, 1988). However, other authors did not observe differences in performance when ionophores were fed via milk replacer or starter (Nussio et al, 2002;Nussio et al, 2003a;Klotz and Heitmann, 2006), probably because -E-mail: lsferreira@ymail.com of variation in the rumen development among evaluated animals. However, even though in several countries sodium monensin is included in most commercial starters, the use of ionophores as growth promoters has been already banned in the European Union, which may be a tendency in other countries.…”
Section: Introductionmentioning
confidence: 99%
“…Os resultados mostram que a monensina não afetou o consumo de concentrado, podendo ser incluída sem prejuízos a programas de desmama precoce baseados no consumo de concentrado, como sugerido por Quigley (1996 b). Entretanto, Nussio et al (2002) observaram redução no consumo de MS em bezerros recebendo monensina em concentrado contendo grão floculado, somente no período após a desmama; sugerindo que o efeito inibidor ocorra somente quando o animal apresenta o rúmen parcialmente desenvolvido.…”
Section: Resultsunclassified
“…As taxas de crescimento animal estiveram abaixo dos padrões recomendados na literatura com vistas à produção de fêmeas de reposição, com peso adequado por volta de 24 meses de idade (Hoffman, 1997). O baixo consumo de concentrado dever estar relacionado com falhas no manejo, principalmente relaciondas ao tipo de cocho dos abrigos individuais, uma vez que Nussio et al (2002) observaram desempenho dentro das recomendações de literatura, fornecendo concentrado similar, formulado com grão floculado e inclusão de monensina.…”
Section: Resultsunclassified
“…They can be added to feed, water or mineral salt and, depending on the drug, its use can be continuous or strategically periodic. Among the most widely use are sulfa, amprolium (SANTIAGO et al, 1977), decoquinate, antibiotics, ionophores (monensin, salinomycin and lasalocid) (HEINRICHS;BUSH, 1991;WAGGONER et al, 1994;NUSSIO et al, 2002;VIEIRA et al, 2004;VIEIRA et al, 2005;LIMA et al, 2009) and toltrazuril (SANTIAGO et al, 1977;SILVA et al, 2007). Decoquinate interrupts the development of coccidians from the outset of their life cycle, by acting on the first stages of their lives to delay their development before they can cause any intestinal damage over the entire period of their life cycle in the small intestine.…”
Section: Introductionmentioning
confidence: 99%